Karakter Morfologi dan Produksi Pati Sagu (Metroxylon spp.) di Kecamatan Tinombo Selatan, Sulawesi Tengah - Pembayun, Putri; Karmanah, Karmanah; Djoefrie, Mochamad Hasjim Bintoro (Universitas Nusa Bangsa, 2024)
Sago (Metroxylon spp.) is carbohydrate-producing plant that has high productivity and potential to developed in Indonesia. Distribution of sago area in the world is 6,279,637 hectares and Indonesia is 5,579,637 hectares. Sago can produce dry much as 20-40 tonnes ha-1 year-1, in Mappi Regency there are sago that have dry starch of 1,197.20 kg steem-1. The distribution of sago in Indonesia is extensive, covering the islands of Sulawesi, Sumatra, Kalimantan, Maluku and Java. This study aimed to obtain information on morphological characters and starch production of several sago accessions in South Tinombo District, Parigi Moutong Regency, Central Sulawesi Province. The research used the obsevation method on fourteen accessions. Sago accessions in The South Tinombo District have different morphological and production characters. Steem length from 5.65-13.10 m. Rachis length from 2.70-6.80 m and petiole length from 0.46-1.66 m. Accession Sigenti has the highest dry starch production. Accession Sigenti had the highest dry starch production of 429.19 kg stem-1 and Accession Sigenti South 2 the lowest of 56.62 kg stem-1. The average dry starch production in Tinombo Selatan sub-district was 245.90 kg stem-1. Accession Sigenti is recommended as a local superior sago and can be further researched for yield stability to become a superior sago variety. Sagu (Metroxylon spp.) merupakan tanaman penghasil karbohidrat yang memiliki produktivitas tinggi dan sangat potensial untuk dikembangkan di Indonesia. Luas pertanaman sagu di dunia 6.279.637 hektar dan Indonesia sekitar 5.579.637 hektar. Penyebaran sagu di Indonesia cukup luas, meliputi Pulau Sulawesi, Sumatra, Kalimantan, Maluku dan Jawa. Sagu dapat menghasilkan pati kering sebanyak 20-40 ton ha-1 tahun-1, di Kabupaten Mappi terdapat pohon sagu yang memiliki kandungan pati kering 1.197,20 kg pohon-1. Penelitian bertujuan untuk mendapatkan informasi mengenai karakter morfologi dan produksi pati beberapa aksesi sagu di Kecamatan Tinombo Selatan, Kabupaten Parigi Moutong, Provinsi Sulawesi Tengah. Penelitian menggunakan metode observasi terhadap empat belas aksesi. Aksesi sagu di Kecamatan Tinombo Selatan memiliki karakter morfologi dan produksi yang berbeda-beda. Panjang batang berkisar antara 5,65-13,10 m. Panjang rachis berkisar antara 2,70-6,80 m dan panjang petiol berkisar antara 0,46-1,66 m. Aksesi Sigenti memiliki produksi pati kering paling tinggi 429,19 kg batang-1 dan Aksesi Sigenti Selatan 2 paling sedikit 56,62 kg batang-1. Rata-rata produksi pati kering di Kecamatan Tinombo Selatan 245,90 kg batang-1. Aksesi Sigenti direkomendasi sebagai sagu unggul lokal dan dapat diteliti lebih lanjut kestabilan hasilnya untuk menjadi varietas sagu unggul.